Complexity and postmodernism : understanding complex systems - Cilliers, Paul, 1956-2011. (London ; New York : Routledge, 1998)
In Complexity and Postmodernism, Paul Cilliers offers us a unique approach to understanding complexity and computational theory by integrating postmodern theory (like that of Derrida and Lyotard) into his discussion.
Chapter 1 Approaching complexity -- chapter 2 Introducing connectionism -- chapter 3 Post-structuralism, connectionism and complexity -- chapter 4 John Searle befuddles -- chapter 5 Problems with representation -- chapter 6 Self-organisation in complex systems -- chapter 7 Complexity and postmodernism -- chapter 8 Afterword: Understanding complexity.
Includes bibliographical references (pages 143-154) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Complexity (Philosophy); Computational complexity; Postmodernism; Complexité (Philosophie); Complexité de calcul (Informatique); Postmodernisme; PHILOSOPHY -- Metaphysics; Complexity (Philosophy); Computational complexity; Postmodernism